1984
DOI: 10.5465/amr.1984.4279673
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity: Toward Conceptual Clarity

Abstract: A model is presented that summarizes existing knowledge concerning job insecurity, points at its deficiencies, and identifies further research needed to understand the nature, causes, and consequences of this increasingly important phenomenon. Such knowledge is crucial because job insecurity is a key element in a positive feedback loop that accelerates organizational decline. Four recent phenomena in the United States have made job insecurity a particularly important variable for organizational scholars to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
573
0
34

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 947 publications
(629 citation statements)
references
References 31 publications
22
573
0
34
Order By: Relevance
“…Furthermore, given the public nature of the allegations, even in a good market, finding another job could have been a tall order for me. Therefore, the threat of losing my job, which I loved dearly, indeed elicited the same reaction as an anticipated death, as Greenhalgh and Rosenblatt (1984) suggest.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Furthermore, given the public nature of the allegations, even in a good market, finding another job could have been a tall order for me. Therefore, the threat of losing my job, which I loved dearly, indeed elicited the same reaction as an anticipated death, as Greenhalgh and Rosenblatt (1984) suggest.…”
Section: Discussionmentioning
confidence: 75%
“…Research has shown that because of the widespread value placed on work, being terminated from work can be traumatic (Spera, Buhrfeind, & Pennebaker, 1994) and can lead to mental illness, suicide, child abuse and hospital admissions (Brenner, 1976). Job insecurity has been defined as perceived powerlessness to maintain desired continuity in a threatened job situation (Greenhalgh & Rosenblatt, 1984). According to Ferrie (2001), job insecurity can be self-perceived or externally attributed, and self-perceived job insecurity is composed of individuals who report their jobs as insecure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations